1987
DOI: 10.1002/ajp.1350120403
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of ovarian cycles within and between social groups in golden lion tamarins (Leontopithecus rosalia)

Abstract: Synchronization of ovarian events has been reported in a number of primate species, with the temporal resolution of synchrony ranging from the occurrence of seasonal breeding within the annual cycle to a close matching of ovarian events within a single ovarian cycle. However, ovarian synchrony has not been reported in a New World primate. The temporal association of ovarian events was examined in female golden lion tamarins (Leontopithecus rosalia) living in the same or different social groups. Ovarian cyclici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…& LOPES FERRARI, 1989;GOLDIZEN et al, 1988;DIETZ et al, 1994;SAVAGE et al, 1996) cannot be tested in this study due to the regular food supply of these monkeys in captivity. Indeed, we cannot explain our results with basis in reproductive synchronism among females as found as occurring for Leontopithecus rosalia (FRENCH & STRIBLEY, 1987) since reproductive physiology studies have never reported this condition to occur for marmosets. Therefore, the existence of significant differences in PPI length as a function of time (month) of pairing, and in IBI length as a function of date of the previous litter birth in our results, appears to represent the way the animals in our colony adjust the births to a specific period of the year.…”
Section: Discussioncontrasting
confidence: 59%
“…& LOPES FERRARI, 1989;GOLDIZEN et al, 1988;DIETZ et al, 1994;SAVAGE et al, 1996) cannot be tested in this study due to the regular food supply of these monkeys in captivity. Indeed, we cannot explain our results with basis in reproductive synchronism among females as found as occurring for Leontopithecus rosalia (FRENCH & STRIBLEY, 1987) since reproductive physiology studies have never reported this condition to occur for marmosets. Therefore, the existence of significant differences in PPI length as a function of time (month) of pairing, and in IBI length as a function of date of the previous litter birth in our results, appears to represent the way the animals in our colony adjust the births to a specific period of the year.…”
Section: Discussioncontrasting
confidence: 59%
“…Due to intense reproductive competition in the species, the dominance relationship among females has been very well studied. However, documentation about escape from inhibition by subordinate calli-thrichid females in laboratory groups (among mothers and daughters or among unrelated females) has shown that reproductive inhibition is not as stringent as thought (7)(8)(9)(10)(11). The escape from inhibition by subordinate females (daughters) was also recorded in a monogamous wild group of common marmosets (12).…”
Section: Introductionmentioning
confidence: 97%
“…Laboratory studies have demonstrated behavioral and physiological suppression of fertility in subordinate female marmosets and tamarins, but the mechanisms appear to vary across species [for examples: Callithrix jacchus, Abbott, 1984; Saguinus fuscicollis, Epple & Katz, 1984; Saguinus oedipus, French et al, 1984; Leontopithecus rosalia, French & Stribley, 1987; Saguinus oedipus, Savage et al, 19881. Few studies have addressed any role that male Callitrichids may have on the enhancement or stimulation of reproductive function in females [see Tardif, 1984;Ziegler et al, 1987b;Widowski et al, 19901.…”
Section: Introductionmentioning
confidence: 98%
“…The onset of ovulatory cycling in pubertal female cotton-top tamarins (Saguinus oedipus) appears to be controlled by an interaction among the suppressive effects of the breeding female and/or other family members and the stimulatory effects of pairing with an unfamiliar male [French et al, 1984;Ziegler et al, 1987b;Widowski et al, 19901. Reproductive hormones remained low and acyclic and scent marking and sexual behavior were rarely observed as long as females lived in their natal groups, but both hormones and behavior changed dramatically after females were removed from their family and paired with an unfamiliar male [French et al, 1984;Savage et al, 1988;Widowski et al, 19901.…”
Section: Introductionmentioning
confidence: 98%